Erosional-denudational valleys and their significance for the reconstruction of the Late Glacial environmental conditions (The Drawsko Lakeland, NW Poland) - Paluszkiewicz, Renata (Quaestiones Geographicae, 2011)
The article presents the morphological-lithological development and operation of dry erosional-denudational valleys located on morainic uplands in the Drawsko Lakeland. A detailed research was carried out on the morainic upland of the Buślarka and Piaski Pomorskie area. A geodetic study made it possible to identify over ten NW-SE and N-S oriented erosional-denudational valleys, clearly marked in the relief. They are small landforms: their length does not exceed 100 m, and the depth of incision reaches 4 m. Their exact morphometric description with the help of GIS methods and a detailed study of lithofacies characteristics of their deposits provided an insight into their operation. They follow a Late Glacial pattern in which Late Vistulian erosion only rejuvenated the already existing older forms.